Corporate Governance and Strategic Disclosure Practice: Evidence from Indonesia - Agung Nur Probohudono; Krisnadi Permana; Dian Perwitasari (Universitas Islam Bandung, 2023)
This research aims to find out the extent to which corporate governance affects the strategic disclosure level in Indonesian manufacturing companies. This study employs managerial ownership, institutional ownership, foreign ownership, independent commissioner composition, and number of commissioner board meetings as independent variables, and leverage and profitability as control variables. The sample companies in this research consists of the manufacturing ones releasing annual report in 2013. The measurement of strategic disclosure level in this research employs Eng and Mak's strategic disclosure index (2003) and integrated into Ho and Taylor's index (2013). The sample of the research consists of 71 Indonesian manufacturing companies during 2013. The sampling technique uses purposive sampling one. The result of the research shows that managerial ownership, institutional ownership, and commissioner board composition affects significantly positively the strategic disclosure. The function of the control variable in this study is as the controller of all variables; in the presence of the control variable, the data estimation result shows that leverage and profitability do not affect significantly the strategic disclosure in Indonesian manufacturing companies.